Efektivitas Penyelenggaraan Sistem Drainase Guna Mengendalikan Banjir di Kota Pontianak berdasarkan Perda Kota Pontianak Nomor 5 Tahun 2016 - Kusryat, Dheanita; Mintarsih, Endah (AL-SULTHANIYAH, 2025)
The rapid physical development, especially in Pontianak Tenggara District, has resulted in a reduction in water catchment areas because open land is covered by concrete and asphalt. This study aims to reveal and analyze the implementation of drainage systems in overcoming flooding in Pontianak City and to determine the factors that influence the implementation of drainage systems in Pontianak City. This research applies a legal review directly to the field by conducting direct observation. Based on the research results, the Pontianak City drainage system has been regulated through Regional Regulation Number 5 of 2016 which covers technical and non-technical aspects with the aim of creating a healthy environment, free from flooding, and supporting water conservation. Its implementation includes the planning, construction, operation, supervision, and evaluation stages carried out by the PUPR Service and reported to the Mayor. Implementation is hampered by low public awareness and limited human resources and infrastructure. Furthermore, law enforcement against violations of regional regulations is inconsistent, and overlapping sanctions persist, preventing optimal achievement of drainage management goals.